2011
DOI: 10.1083/jcb.201010117
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation inhibits α-synuclein aggregation and toxicity

Abstract: Sumoylation of α-synuclein decreases its rate of aggregation and its deleterious effects in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(217 citation statements)
references
References 57 publications
6
209
0
2
Order By: Relevance
“…Alternatively, posttranslational chemical modifications might explain the difference between MSA and PD inocula. Ubiquitination, phosphorylation, nitrosylation, and sumoylation of α-synuclein have all been reported to play a role in α-synuclein toxicity (47)(48)(49)(50).…”
Section: The Incubation Time For the Tgm83mentioning
confidence: 99%
“…Alternatively, posttranslational chemical modifications might explain the difference between MSA and PD inocula. Ubiquitination, phosphorylation, nitrosylation, and sumoylation of α-synuclein have all been reported to play a role in α-synuclein toxicity (47)(48)(49)(50).…”
Section: The Incubation Time For the Tgm83mentioning
confidence: 99%
“…Presumably, α-synuclein prion strains represent different conformers, but currently we must entertain the possibility that a posttranslational chemical modification distinguishes one strain from another. Notably, ubiquitination, phosphorylation, nitrosylation, and sumoylation have all been reported to be covalently bound to α-synuclein (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…14,42 It has been reported that sumoylation can modulate the clustering or cooperative binding of proteins. [22][23][24][25] Our evidence suggest a similar mechanism for the control of condensin clustering as excess sumoylation (smt4D) results in pericentric condensin declustering (Fig. 6).…”
Section: 38mentioning
confidence: 83%
“…It has been found that sumoylation can keep proteins from aggregating or clustering. [22][23][24][25] Sumoylation sites have been found on Top2, cohesin, and condensin. 19 Previously, we have shown that condensin clusters in the pericentromere.…”
Section: Smt4 Aids Condensin Clustering In the Pericentromerementioning
confidence: 99%